PD-1 and TIGIT coexpression identifies a circulating CD8 T cell subset predictive of response to anti-PD-1 therapy - Paul Nghiem; Martin Cheever; Stanley R Riddell; Steven P Fling; Nirasha Ramchurren; Nathalie Labarrière; Sylvain Simon; Virginie Vignard; Tiffany Beauvais; Brigitte Dreno; Valentin Voillet; Zhong Wu; et al. (Journal for ImmunoTherapy of Cancer)
Background Clinical benefit from programmed cell death 1 receptor (PD-1) inhibitors relies on reinvigoration of endogenous antitumor immunity. Nonetheless, robust immunological markers, based on circulating immune cell subsets associated with therapeutic efficacy are yet to be validated.Methods We isolated peripheral blood mononuclear cell from three independent cohorts of melanoma and Merkel cell carcinoma patients treated with PD-1 inhibitor, at baseline and longitudinally after therapy. Using multiparameter flow cytometry and cell sorting, we isolated four subsets of CD8+ T cells, based on PD-1 and TIGIT expression profiles. We performed phenotypic characterization, T cell receptor sequencing, targeted transcriptomic analysis and antitumor reactivity assays to thoroughly characterize each of these subsets.Results We documented that the frequency of circulating PD-1+TIGIT+ (DPOS) CD8+ T-cells after 1 month of anti-PD-1 therapy was associated with clinical response and overall survival. This DPOS T-cell population was enriched in highly activated T-cells, tumor-specific and emerging T-cell clonotypes and T lymphocytes overexpressing CXCR5, a key marker of the CD8 cytotoxic follicular T cell population. Additionally, transcriptomic profiling defined a specific gene signature for this population as well as the overexpression of specific pathways associated with the therapeutic response.Conclusions Our results provide a convincing rationale for monitoring this PD-1+TIGIT+ circulating population as an early cellular-based marker of therapeutic response to anti-PD-1 therapy.